Biodegradable polymers for industrial applications - Smith, Ray (Woodhead ; CRC Press, 2005)
The vast majority of plastic products are made from petroleum-based synthetic polymers that do not degrade in a landfill or in a compost-like environment. Therefore, the disposal of these products poses a serious environmental problem. An environmentally-conscious alternative is to design/synthesize polymers that are biodegradable. In this authoritative new book fundamental concepts concerning the development of biodegradable polymers, degradable polymers from sustainable sources, degradation and properties and industrial applications and their importance are reviewed.